2001
DOI: 10.1021/nl015604v
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Two-Dimensional Assemblies of Ag Nanoparticles and Nanocavities in Poly(dimethylsiloxane) Resin

Abstract: Silver nanoparticles, self-assembled in two-dimensional arrays on quartz and silicon surfaces, were coated with poly(dimethylsiloxane) (PDMS). After peeling off the surface, resin films contained embedded nanoparticles in their original arrangement. Films with nanoparticles are transparent, flexible, and mechanically stable. The embedded nanoparticles were etched away, producing nanocavities in PDMS. The described method can be used to produce highly robust assemblies of metal, semiconductor, and dielectric na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 14 publications
(19 reference statements)
0
40
0
Order By: Relevance
“…10d-f). 43 The approach of using a resist can also be used to fabricate nanoparticle arrays on layer-by-layer (LBL) films. 44,45 LBL assembly is an effective and versatile technique to fabricate thin multilayer films.…”
Section: Alignment Of Nanoparticlesmentioning
confidence: 99%
“…10d-f). 43 The approach of using a resist can also be used to fabricate nanoparticle arrays on layer-by-layer (LBL) films. 44,45 LBL assembly is an effective and versatile technique to fabricate thin multilayer films.…”
Section: Alignment Of Nanoparticlesmentioning
confidence: 99%
“…One interesting point is that the membrane containing metallic silver nanoparticles still had a selectivity of 31 and, although it was less than the initial value of 52, this suggests that the metallic silver nanoparticles which were formed, and in particular their surface, could also act as an olefin carrier for facilitated transport. In this regard, metallic silver nanoparticles utilized in various fields [7][8][9][10][11] were first used as a new olefin carrier for facilitated olefin transport, resulting in a selectivity of 11 for propylene/propane mixtures which remained unchanged for 105 h. It was found that the separation performance was mostly associated with the surface area and partial positive charge of the silver nanoparticles, where the large surface area was obtained from nanoparticles and the partial positive charge on the metallic silver surface was induced by an electron acceptor such as p-benzoquinone or ionic liquid [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] For example, Claus et al reported the particle size effect of Ag/SiO 2 and Ag/TiO 2 catalysts on hydrogenation of crotonaldehyde. Tada et al reported that when 0.24 wt% of Ag nanoclusters was loaded on TiO 2 , the reduction of bis(2-dipyridyl)disulfide (RSSR) to 2-mercaptopyridine by H 2 O was significantly enhanced concomitantly by a 17.9-fold increase in the saturated adsorption amount of RSSR due to specific Ag-S interaction.…”
Section: Introductionmentioning
confidence: 99%